Effects of Durian Seed (Durio zibethinus) Extract on Intestinal Morphometry and Performance of Heat-Stressed Broiler Chickens - Suriansyah, Suriansyah; Hikmawaty, Hikmawaty; Septaningsih, Andi Citra; Sukoco, Hendro; Irmayanti, Irmayanti; Ris, Adryani; Mukhlisah, Andi Nurul; Marsudi, Marsudi; Ramdaniah, Putri (Jurnal Ilmu Ternak Universitas Padjadjaran, 2025)
This trial was therefore undertaken to investigate the effect of durian (dario zibethinus) seed extract supplementation on the growth performance, carcass yield and internal organ development in broilers under heat temperature. 5 treatment groups, including control group (P0) with no extract addition and 4 treatments (P1- P4), where the levels of durian seed extracts used were added into-drinking water at dose concentrations of Nil, 1.0 mL/L, 1.5 mL/L, 2.0 mL/L and 2.5ml/L respectively. Weight gain, feed conversion efficiency, weights of slaughter body parts (and as their relative proportion: liver, heart, proventriculus and gizzard) and internal organs (total intestines) were evaluated. The durian seed meal extract also significantly enhanced (P < 0.05) the body and carcass weights and growth of digestive and metabolic organs. Values were higher in P4 indicating a dose relation. The beneficial health effects are attributed to the bio-active compounds (polyphenols, flavonoinds and phenolic acid) as natural anti oxidants and phyto-biotics which avoid the oxidative stress and stimulate to absorb the nutrient. It is thus justified to conclude that durian seed extract at 2.5 ml/L could be applied as natural growth promoter combined with antioxidative activity in broiler raised under the tropical heat stress source.